Preparation method of down heat storage fabric based on core-shell structure

By spraying and depositing silicon oxygen materials in down heat-reserving fabrics and combining tea polyphenols and crosslinking agents, the problem of degradation of stability and antibacterial properties of volcanic rock composite powders is solved, and the long-term stability and antibacterial effect of the fabric are improved. , avoiding powder removal and aging.

CN119308133AInactive Publication Date: 2025-01-14BOSIDENG DOWN WEAR LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411741297.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the long-term use and washing of existing down heat-storage fabrics, zinc ion loss leads to a decrease in antibacterial properties, and inert volcanic rock composite powder leads to depowder, affecting the stability and aging of the fabric.

Method used

Spraying method is used to deposit silicon oxygen materials on volcanic rock composite powder, and the surface activity is formed through ultrasonic and aqueous ethanol solution, combining tea polyphenols and crosslinking agents to form a composite antibacterial system, which improves the stability of volcanic rock composite powder and Antibacterial properties.

Benefits of technology

It significantly improves the stability and antibacterial properties of volcanic rock composite powder, reduces bacterial deposition, extends the service life of the fabric, avoids depowder and aging problems after washing, and maintains excellent antibacterial stability and thermal insulation effect.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of down feather fabrics, and particularly relates to a preparation method of a down feather heat storage fabric based on a core-shell structure, and the method comprises the following steps: carrying out silanization surface modification on volcanic rock composite powder, forming a soaking solution with an ethanol aqueous solution, tea polyphenol and a cross-linking agent, and finally carrying out padding treatment on a basic fabric to obtain the down feather heat storage fabric. According to the preparation method, the stability problem of existing volcanic rock composite powder is solved, deposition of a silica material on the volcanic rock composite powder is achieved in a spraying mode, surface activity is formed after hydrolytic polycondensation, and therefore the stability of the volcanic rock composite powder on the surface material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of down fabrics, and in particular relates to a method for preparing a down heat storage fabric based on a core-shell structure. Background Art

[0002] There are many thermal insulation fabrics on the market. Generally, during the spinning process, an appropriate amount of light-absorbing and heat-storing particles that can convert sunlight into far-infrared rays are added to the fibers to obtain light-absorbing and heat-storing fibers. The thermal insulation effect is achieved through the light-absorbing and heat-storing effect, and then the thermal insulation fabrics are woven through the light-absorbing and heat-storing fibers; or, a layer of material that absorbs light energy and converts it into thermal energy is coated on the surface of the fabric to form a good thermal insulation layer.

[0003] Volcanic rock composite powder is one of the representative materials of light-absorbing heat-storing particles. Volcanic rock composite powder is rich in far-infrared ceramic powder, has a special microporous structure and a strong heat-absorbing area, can quickly absorb and store the heat emitted by the human body, thereby improving the heat storage capacity of the fabric and keeping the body warm. At the same time, volcanic rock composite powder is rich in zinc ions, which can inhibit the growth of bacteria. However, with the long-term use of down heat-storing fabrics, washing is an indispensable aspect. During the continuous washing process, zinc ions will gradually be lost, resulting in a decrease in antibacterial performance. At the same time, the volcanic rock composite powder itself has a certain inertia. After washing, the number of drying times increases, the fabric gradually ages, and it will cause powder shedding, that is, causing the volcanic rock composite powder to fall off. Summary of the invention

[0004] In view of the problems in the prior art, the present invention provides a method for preparing down thermal storage fabric based on a core-shell structure, which solves the stability problem of the existing volcanic rock composite powder. The silicon oxide material is deposited on the volcanic rock composite powder by spraying, and the surface activity is formed after hydrolysis and condensation, thereby improving the stability of the volcanic rock composite powder on the fabric.

[0005] In order to achieve the above technical objectives, the technical solution of the present invention is: A method for preparing a down heat storage fabric based on a core-shell structure comprises the following steps: Step 1, placing the volcanic rock composite powder in an ethanol aqueous solution and ultrasonicating it for 10-20 minutes, filtering and drying to obtain a clean volcanic rock composite powder; then spraying the ether solution containing silane on the volcanic rock composite powder, filtering and standing at a constant temperature for 20-30 minutes to obtain a modified volcanic rock composite powder, wherein the ethanol concentration in the ethanol aqueous solution is 50-60%, the concentration of the volcanic rock composite powder in the ethanol aqueous solution is 400-500g / L, the ultrasonic temperature is 20-30°C, the ultrasonic frequency is 60-80kHz, and the drying temperature is 120-140°C; the silane concentration in the ether solution is 90-120g / L, and the silane is triethyl chloropropane The temperature of the constant temperature static state is 100-120° C., the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1; this step utilizes the high-frequency vibration of ultrasound and the solubility and exfoliation of the ethanol aqueous solution to ensure that the ethanol aqueous solution enters the porous structure of the volcanic rock composite powder, achieves the effect of internal and external cleaning, completely exfoliates the surface impurities, and improves the cleanliness of the volcanic rock composite powder; the ether liquid forms a liquid film on the surface of the volcanic rock composite powder in a spraying manner, and the liquid film will not penetrate into the inner layer due to the problem of internal bubbles, and only forms a liquid film on the surface. Therefore, the silane only stays on the surface, and the constant temperature static state after filtration can form in-situ hydrolysis and ether evaporation, And based on this temperature, the in-situ hydrolyzed silane will form an in-situ polycondensation, thereby converting the silane into a hydroxyl-containing silicon-oxygen material. This treatment realizes the change of the hydrophilicity and positive charge of the surface of the volcanic rock composite powder, while improving the surface inertness, ensuring the surface activity of the volcanic rock composite powder, and does not affect the pore structure and self-performance of the volcanic rock composite powder; the volcanic rock composite powder is ground before use to achieve powderization and uniform particle size of the volcanic rock composite powder; Step 2, adding tea polyphenols, a cross-linking agent and a modified volcanic rock composite powder to an ethanol aqueous solution and stirring evenly to obtain a soaking liquid, wherein the mass ratio of the soaking liquid is: 8-10 parts of tea polyphenols, 3-5 parts of a cross-linking agent, 10-15 parts of a modified volcanic rock composite powder, and 30-40 parts of an ethanol aqueous solution, wherein the volume fraction of ethanol in the ethanol aqueous solution is 40-50%, and the stirring speed for the uniform stirring is 100-500r / min; the cross-linking agent is HOLPOSON® HFM-2; Step 3, putting the basic fabric into the soaking liquid for immersion and rolling treatment, taking it out and drying it to obtain the down heat storage fabric; the mass ratio of the basic fabric to the soaking liquid is 1:5-10, the immersion and rolling treatment adopts two immersions and two rollings, the temperature is 50-60°C, the drying temperature is 110-130°C, and the time is 5-10min; the basic fabric is woven into the basic fabric with nylon fiber and polyester fiber, and the mass ratio of nylon fiber to polyester fiber is 3:1.

[0006] It can be seen from the above description that the present invention has the following advantages: 1. The present invention solves the stability problem of existing volcanic rock composite powders, and uses a spraying method to achieve the deposition of silicon-oxygen materials on the volcanic rock composite powders, and forms surface activity after hydrolysis and polycondensation, thereby improving the stability of the volcanic rock composite powders on the fabric; 2. The present invention adopts ethanol aqueous solution as the solvent of the soaking liquid, realizes the homogeneous dispersion of the volcanic rock composite powder and tea polyphenols, forms a composite antibacterial system after deposition and solidification, thereby achieving excellent antibacterial properties; 3. The present invention adopts the method of silicon-oxygen modification to transform the positive charge on the surface of the volcanic rock composite powder, thereby reducing the deposition adsorption of microorganisms and effectively inhibiting bacterial deposition. At the same time, silicon-oxygen modification can effectively enhance chemical connectivity, and cooperate with the coupling agent and the hydroxyl structure of tea polyphenols to form excellent curing properties. DETAILED DESCRIPTION

[0007] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention. Example 1

[0008] A method for preparing a down heat storage fabric based on a core-shell structure comprises the following steps: Step 1, placing the volcanic rock composite powder in an ethanol aqueous solution and ultrasonicating it for 10 minutes, filtering and drying to obtain a clean volcanic rock composite powder; then spraying the ether solution containing silane on the volcanic rock composite powder, filtering and standing at a constant temperature for 20 minutes to obtain a modified volcanic rock composite powder, wherein the ethanol concentration in the ethanol aqueous solution is 50%, the concentration of the volcanic rock composite powder in the ethanol aqueous solution is 400g / L, the ultrasonic temperature is 20°C, the ultrasonic frequency is 60kHz, and the drying temperature is 120°C; the silane concentration in the ether solution is 90g / L, the silane is triethoxysilane chloropropane, the constant temperature standing temperature is 100°C, the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1; Step 2, adding tea polyphenols, a cross-linking agent and a modified volcanic rock composite powder into an ethanol aqueous solution and stirring evenly to obtain a soaking liquid, wherein the mass ratio of the soaking liquid is: 8 parts of tea polyphenols, 3 parts of a cross-linking agent, 10 parts of a modified volcanic rock composite powder, and 30 parts of an ethanol aqueous solution, wherein the volume fraction of ethanol in the ethanol aqueous solution is 40%, and the stirring speed for the uniform stirring is 100 r / min; the cross-linking agent is HOLPOSON® HFM-2; Step 3, putting the basic fabric into the soaking liquid for immersion and rolling treatment, taking it out and drying it to obtain the down heat storage fabric; the mass ratio of the basic fabric to the soaking liquid is 1:5, the immersion and rolling treatment adopts two immersions and two rollings, the temperature is 50°C, the drying temperature is 110°C, and the time is 5 minutes; the basic fabric is woven into the basic fabric with nylon fiber and polyester fiber, and the mass ratio of nylon fiber to polyester fiber is 3:1. Example 2

[0009] A method for preparing a down heat storage fabric based on a core-shell structure comprises the following steps: Step 1, placing the volcanic rock composite powder in an ethanol aqueous solution and ultrasonicating it for 20 minutes, filtering and drying to obtain a clean volcanic rock composite powder; then spraying the ether solution containing silane on the volcanic rock composite powder, filtering and standing at a constant temperature for 30 minutes to obtain a modified volcanic rock composite powder, wherein the ethanol concentration in the ethanol aqueous solution is 60%, the concentration of the volcanic rock composite powder in the ethanol aqueous solution is 500g / L, the ultrasonic temperature is 30°C, the ultrasonic frequency is 80kHz, and the drying temperature is 140°C; the silane concentration in the ether solution is 120g / L, the silane is triethoxysilane chloropropane, the constant temperature standing temperature is 120°C, the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1; Step 2, adding tea polyphenols, a cross-linking agent and a modified volcanic rock composite powder into an ethanol aqueous solution and stirring evenly to obtain a soaking liquid, wherein the mass ratio of the soaking liquid is: 10 parts of tea polyphenols, 5 parts of a cross-linking agent, 15 parts of a modified volcanic rock composite powder, and 40 parts of an ethanol aqueous solution, wherein the volume fraction of ethanol in the ethanol aqueous solution is 50%, and the stirring speed for the uniform stirring is 500 r / min; the cross-linking agent is HOLPOSON® HFM-2; Step 3, putting the basic fabric into the soaking liquid for immersion and rolling treatment, taking it out and drying it to obtain the down heat storage fabric; the mass ratio of the basic fabric to the soaking liquid is 1:10, the immersion and rolling treatment adopts two immersions and two rollings, the temperature is 60°C, the drying temperature is 130°C, and the time is 10min; the basic fabric is woven into the basic fabric with nylon fiber and polyester fiber, and the mass ratio of nylon fiber to polyester fiber is 3:1. Example 3

[0010] A method for preparing a down heat storage fabric based on a core-shell structure comprises the following steps: Step 1, placing the volcanic rock composite powder in an ethanol aqueous solution and ultrasonicating it for 15 minutes, filtering and drying to obtain a clean volcanic rock composite powder; then spraying the ether solution containing silane on the volcanic rock composite powder, filtering and standing at a constant temperature for 25 minutes to obtain a modified volcanic rock composite powder, wherein the ethanol concentration in the ethanol aqueous solution is 55%, the concentration of the volcanic rock composite powder in the ethanol aqueous solution is 450g / L, the ultrasonic temperature is 25°C, the ultrasonic frequency is 70kHz, and the drying temperature is 130°C; the silane concentration in the ether solution is 100g / L, the silane is triethoxysilane chloropropane, the constant temperature standing temperature is 110°C, the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1; Step 2, adding tea polyphenols, a cross-linking agent and a modified volcanic rock composite powder into an ethanol aqueous solution and stirring evenly to obtain a soaking liquid, wherein the mass ratio of the soaking liquid is: 9 parts of tea polyphenols, 4 parts of a cross-linking agent, 12 parts of a modified volcanic rock composite powder, and 35 parts of an ethanol aqueous solution, wherein the volume fraction of ethanol in the ethanol aqueous solution is 45%, and the stirring speed for the uniform stirring is 300 r / min; the cross-linking agent is HOLPOSON® HFM-2; Step 3, putting the basic fabric into the soaking liquid for immersion and rolling treatment, taking it out and drying it to obtain the down heat storage fabric; the mass ratio of the basic fabric to the soaking liquid is 1:8, the immersion and rolling treatment adopts two immersions and two rollings, the temperature is 55°C, the drying temperature is 120°C, and the time is 8 minutes; the basic fabric is woven into the basic fabric with nylon fiber and polyester fiber, and the mass ratio of nylon fiber to polyester fiber is 3:1.

[0011] Comparative Example A method for preparing a down heat storage fabric based on a core-shell structure comprises the following steps: Step 1, adding tea polyphenols, a cross-linking agent and a volcanic rock composite powder into an ethanol aqueous solution and stirring evenly to obtain a soaking liquid, wherein the mass ratio of the soaking liquid is: 9 parts of tea polyphenols, 4 parts of a cross-linking agent, 12 parts of a volcanic rock composite powder, and 35 parts of an ethanol aqueous solution, wherein the volume fraction of ethanol in the ethanol aqueous solution is 45%, and the stirring speed for the uniform stirring is 300 r / min; the cross-linking agent is HOLPOSON® HFM-2; Step 2, putting the basic fabric into the soaking liquid for immersion and rolling treatment, taking it out and drying it to obtain the down heat storage fabric; the mass ratio of the basic fabric to the soaking liquid is 1:8, the immersion and rolling treatment adopts two immersions and two rollings, the temperature is 55°C, the drying temperature is 120°C, and the time is 8 minutes; the basic fabric is woven into the basic fabric with nylon fiber and polyester fiber, and the mass ratio of nylon fiber to polyester fiber is 3:1.

[0012] Performance Testing The down heat storage fabrics of Examples 1-3 and the comparative example were used as test samples to perform the following performance tests, and the results are as follows: Example 1 Example 2 Example 3 Comparative Example Antibacterial rate >99.9% >99.9% >99.9% >99.9% Antibacterial rate after washing 100 times 99.89% 99.94% 99.91% 93.17% Insulation rate 48% 49% 49% 37% Heat preservation rate after 100 washes 43% 45% 44% 31% Appearance after washing and drying 1000 times No cracks and powder loss No cracks and powder loss No cracks and powder loss Edge cracks, no powder loss Among them, the antibacterial rate uses Escherichia coli as the test bacteria.

[0013] The above data show that the technical solution effectively improves the protection of the volcanic rock composite powder by silicon-oxygen modification, which not only improves the connection stability of the volcanic rock composite powder and maintains stable performance during washing, but also does not cause powder loss and cracking during aging. Compared with the edge cracks in the comparative example, it shows excellent aging resistance. At the same time, the fabric of the technical solution has excellent antibacterial properties and antibacterial stability, reducing the problem of bacterial deposition.

[0014] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a down heat storage fabric based on a core-shell structure, characterized in that: The steps include: Step 1, placing the volcanic rock composite powder in an ethanol aqueous solution and ultrasonicating for 10-20 minutes, filtering and drying to obtain clean volcanic rock composite powder; then spraying ether solution containing silane on the volcanic rock composite powder, filtering and standing at a constant temperature for 20-30 minutes to obtain modified volcanic rock composite powder; Step 2, adding tea polyphenols, a cross-linking agent and a modified volcanic rock composite powder into an ethanol aqueous solution and stirring the mixture to obtain a soaking solution; Step 3, putting the base fabric into the soaking liquid for padding treatment, taking it out and drying it to obtain the down heat storage fabric.

2. The method for preparing the down heat storage fabric based on the core-shell structure according to claim 1, characterized in that: The ethanol concentration in the ethanol aqueous solution in step 1 is 50-60%, the concentration of the volcanic rock composite powder in the ethanol aqueous solution is 400-500 g / L, the temperature of the ultrasound is 20-30° C., the frequency of the ultrasound is 60-80 kHz, and the temperature of the drying is 120-140° C.

3. The method for preparing the down heat storage fabric based on the core-shell structure according to claim 1, characterized in that: The silane concentration in the ether solution in step 1 is 90-120 g / L, the silane is triethoxy chloropropane silane, the constant temperature is 100-120° C., the atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:

1.

4. The method for preparing the down heat storage fabric based on the core-shell structure according to claim 1, characterized in that: The volcanic rock composite powder in step 1 is ground before use to achieve powderization and uniform particle size of the volcanic rock composite powder.

5. The method for preparing the down heat storage fabric based on the core-shell structure according to claim 1, characterized in that: The mass ratio of the soaking liquid in step 2 is: 8-10 parts of tea polyphenols, 3-5 parts of cross-linking agent, 10-15 parts of modified volcanic rock composite powder, and 30-40 parts of ethanol aqueous solution.

6. The method for preparing the down heat storage fabric based on the core-shell structure according to claim 1, characterized in that: The volume fraction of ethanol in the ethanol aqueous solution in step 2 is 40-50%, and the stirring speed for uniform stirring is 100-500r / min.

7. The method for preparing the down heat storage fabric based on the core-shell structure according to claim 1, characterized in that: The crosslinking agent in step 2 is HOLPOSON® HFM-2.

8. The method for preparing the down heat storage fabric based on the core-shell structure according to claim 1, characterized in that: The mass ratio of the base fabric to the soaking liquid in step 3 is 1:5-10, the padding treatment adopts double dipping and double padding, the temperature is 50-60° C., the drying temperature is 110-130° C., and the time is 5-10 min.

9. The method for preparing the down heat storage fabric based on the core-shell structure according to claim 1, characterized in that: The basic fabric in step 3 is woven from nylon fiber and polyester fiber, and the mass ratio of the nylon fiber to the polyester fiber is 3:1.

Citation Information

Patent Citations

  • Aerogel volcanic rock thermal insulation filling material for cotton clothes

    CN115748095A

  • Volcanic rock heating fabric and preparation method thereof

    CN116080205A

  • Volcanic rock antibacterial thermal fabric based on down jacket and preparation method of volcanic rock antibacterial thermal fabric

    CN117144535A

  • Antibacterial aerogel down fabric and preparation method thereof

    CN118292258A